Edukasi Pengolahan Bayam sebagai Sumber Pangan Sehat di Masyarakat Saat Ini - Rananda Septanta; Baharudin Saga; Khuzaeni Khuzaeni; Sairin Sairin (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This Community Service Program (PKM) focuses on education regarding spinach processing as a healthy food source in contemporary society, especially for households. Spinach is widely available but its utilization in daily diets remains limited despite its high nutritional value in Indonesia. The objective of this activity is to increase community knowledge and skills in processing spinach into nutritious food products through community training. The PKM was conducted at Pamulang Permai Housing, Pamulang Barat, South Tangerang on April 11, 2026, involving 10 lecturers from Universitas Pamulang and 20 PKK women participants through preparation, implementation, and reporting stages with coordinated team planning, active community involvement, and structured program execution to ensure effective outcomes and sustainability of activities results. The implementation used presentation, hands-on practice, discussion, and question-and-answer sessions, following preparation, implementation, and reporting stages to enhance understanding supported by practical demonstrations and interactive learning media that encouraged participant engagement and motivation improvement. The results showed increased understanding and enthusiasm among participants in processing spinach into various healthy food innovations and practical skills. Participants were able to apply simple processing techniques and showed interest in continuing healthy food practices at home in future.